ANALYSIS OF CLIMATE CHANGE VULNERABILITY OF RICE FARMERS IN ACEH UTARA DISTRICT - Maulana I.; Azhar; Romano (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
Climate change's impact on Indonesia's agricultural sector is now increasingly felt. The potential danger of climate change for the agricultural sector is the decline in rice production. District Aceh Utara, the most extensive rice production center in Aceh Province, has a high hazard potential and is one of the criteria for Regional Vulnerability and a High District/City Disaster Risk Index (IRBI). This study aims to determine the level of vulnerability to climate change on the income of rice farmers in District Aceh Utara. This study involved 100 farmers in Baktiya and Lhoksukon sub-districts who were determined using the multi-stage Stratification Random Sampling Technique. The data analysis technique used is the vulnerability level analysis model. The results showed that rice farmers in Aceh Utara District tended to be at a low level of vulnerability. Rice farmers in District Aceh Utara could maintain and save their farms from the stress of climate change.